2014
DOI: 10.1016/j.jpedsurg.2014.02.060
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal bleeding as a complication of serial transverse enteroplasty

Abstract: Purpose Serial transverse enteroplasty (STEP) lengthens and tapers bowel in patients with intestinal failure and has a generally low complication profile. Evaluation and treatment of serious gastrointestinal bleeding (GIB) in three STEP patients is described. Methods Records of patients participating in an interdisciplinary intestinal rehabilitation program were reviewed to identify those who underwent STEP and had GIB necessitating red blood cell transfusion. Results Of 296 patients, 23 underwent STEP and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 22 publications
(29 reference statements)
1
6
0
Order By: Relevance
“…6 7 8 Infrequent but worrisome, the apparition of ulcerations along the staple line months or years after surgery has been described and leads to chronic gastrointestinal bleeding and transfusion requirement. 7 12 13 14 Of unknown origin, as is in our case, they appear more in the distal staple lines, closer to the colonic anastomosis, suggesting bacterial overgrowth as one of the possible etiologic factors. 12 14…”
Section: Discussionsupporting
confidence: 52%
“…6 7 8 Infrequent but worrisome, the apparition of ulcerations along the staple line months or years after surgery has been described and leads to chronic gastrointestinal bleeding and transfusion requirement. 7 12 13 14 Of unknown origin, as is in our case, they appear more in the distal staple lines, closer to the colonic anastomosis, suggesting bacterial overgrowth as one of the possible etiologic factors. 12 14…”
Section: Discussionsupporting
confidence: 52%
“…Corticosteroids, given early in the course of illness, seem to produce consistent benefits for gastrointestinal bleeding, in children suffering from HSP [ 18 ]. Remarkably, our patient also had congenital malrotation of the intestine, which could increase the risk of gastrointestinal bleeding [ 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have revealed that patients underwent STEP may develop gastrointestinal hemorrhage. 16 A single institution series report on the STEP procedure by Ching et al 17 revealed that 3 out of the 16 patients followed had gastrointestinal bleed that did not require reoperation. The underlying cause for these bleeds was not described.…”
Section: Discussionmentioning
confidence: 99%